FAKTOR RISIKO YANG MEMPENGARUHI METODE PERSALINAN DI RSUP DR. M. DJAMIL PADANG TAHUN 2017 – 2020 - Alvin, Alfannya; Yusrawati, Yusrawati; Nurhayati, Nurhayati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Delivery can be divided into vaginal and perabdominal methods of delivery that can be performed for the process of expelling the baby with the placenta and fetus. The method of delivery has a reason why it is done based on the conditions that affect it. This study aims to determine the risk factors that affect the delivery method in Dr. RSUP. M. Djamil Padang. This type of research is a retrospective descriptive using medical records of mothers who gave birth. This research was conducted at Dr. RSUP. M. Djamil Padang in August 2022 with a total sample of 90 samples in 2017 – 2020. The data used are secondary data from medical records using proportional stratified sampling technique. This study showed that abdominal deliveries were the most common (75.5%), with maternal age conditions being 20-35 years (73.3% and 60%), multipara (40% and 44.4%), secondary education (64.4%). % and 60%), residence in the village (55.6% and 62.2%), preterm and term pregnancy (48.9% vaginally), and term (57.8% abdominal), history of CS, eclampsia /preeclampsia, and COVID-19 (17.1% vaginally) and eclampsia/preeclampsia (29.3% perabdominal), and PROM (30.5% vaginally) and location abnormalities (23.3% perabdominal). Abdominal deliveries mostly occur due to emergency measures (68.9%), elective-probability (100%), medical indications (100%), and multiple indications (66.7%).